Inter- and Intra- Rater Reliability of Navicular Drop Tests Position - 김소연; 유정은; 우다현; 정보영; 최보람 (대한물리치료과학회지, 26(1), 2019)
Background: Pes planus, or flat foot, causes lower limb malalignment and foot pain during walking or exercise. Therefore, a highly reliable evaluation method to accurately diagnose flat feet is necessary. This study investigated the intra-and inter-rater reliability of the navicular drop test in different postures. Design: Cross sectional study. Methods: Forty healthy volunteers performed the navicular drop test in three different combinations of non-weight-bearing and weight-bearing postures (standing/standing, sitting/sitting, and sitting/standing). Two examiners alternately performed the measurements five times in each subject, and in each posture. Significant differences in measurements were obtained among the three postures, with the highest navicular drop being observed in the sitting/standing posture. Results: Inter-rater reliability was high in the sitting/standing and sitting/sitting postures. Intra-rater reliability was high in all three postures. In the sitting/sitting and sitting/standing postures, large navicular drop values and high inter- and intra-rater reliability were observed. Conclusion: Therefore, the sitting/standing and sitting/sitting postures are recommended for use in navicular drop tests to diagnose flat feet. KCI Citation Count: 0